How Technology Facility to Improve Numeracy in Riau Province - Dola Julianti; Syahrul Imardi (UIR PRESS, 2023)
The increase in numeracy in Indonesia depends on the facilities' quality at schools. This study aims to evaluate the technology facilities to improve the numeracy ability of students in Riau Province. The district to be the participant was Junior high schools of Dumai District. The research participant was teachers and students. The collection data techniques were interviews, observation, and documentation. The key instrument in this research was the researchers that gave questions to participants to get data about how the technology facility improves the numeracy of Students at Dumai District. The data analysis technique used in this research was analysis proposed by Creswell (2014). Results show that many facilities to increase numeration are still bad. Technology to improve students’ numeracy is not yet adequate because Dumai must improve public facilities such as highways, Harbor, markets and etc. The government is limiting the budget to help schools.